KESEMPATAN KERJA KARYAWAN PEREMPUAN PADA PT. BARA BATU AMPAR PRIMA (BBAP) DI DESA BATU AMPAR, KECAMATAN KEMUNING KABUPATEN INDRAGIRI HILIR - Siti Almunaroh; Indrawati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This research was carried out in Batu Ampar Village, Kemuning Disteict, Indragiri Hilir Regency. The purpose of this study is to find out the reasons why female employees choose to work at PT. Bara Batu Ampar Prima and income utilization of female employees. The topic of focus in this study is the reason for choosing to work and the use of income, the sample in this study amounted to 25 people. Researchers use descriptive quantitative methods and use census techniques. The data instruments are observation, questionnaires and documentation. This study provides an explanation that female employees also get job opportunities at PT. Bara Batu Ampar Prima (BBAP), so there is a reason female employees choose to work at PT. Bara Batu Ampar Prima (BBAP) is driven by motivation to work there are several needs namely :physiological needs, safety needs, social needs, esteem or status needs, and self actualization needs. This needs causes female employees to choose to work at PT. Bara Batu Ampar Prima (BBAP), so that with the work of female employees their income can be utilized both for the family or household economy and for themselves.Keywords: job opportunities, reasons for choosing to work, income utilization